Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/adem.201700487
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Strength and Ductility in Mg–Zn–Ce Alloy through Achieving High Density Precipitates and Texture Weakening

Abstract: The microstructure with weak fiber texture and dense precipitates is designed and produced through extrusion and subsequent ageing treatment of Mg-6Zn-0.2Ce (wt%) alloy. Results show that ageing treatment improves the strength of the as-extruded Mg-6Zn-0.2Ce (wt%) alloy and retains the ductility. The peak-aged alloy exhibits a good combination of strength and ductility, which is superior to the commercial Mg alloy. The yield strength and elongation to fracture of the peak-aged Mg-6Zn-0.2Ce (wt%) alloy are 225 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Among rare-earth element, many researchers reported that micro-alloying Mg-Zn with yttrium or cerium exhibited a comparable ductility and formability with commercial magnesium alloys. Tables 3 and 4 summarize the mechanical properties of the published alloys in Mg-Zn-Y [154][155][156][157] and Mg-Zn-Ce [48,71,81,85,[156][157][158], respectively. The addition of yttrium to Mg-Zn alloys enhances the formation of magnesium solid solution in ternary systems due to high solid solubility of yttrium in magnesium.…”
Section: Mechanical Properties Of Mg-zn-{ce Y} Alloysmentioning
confidence: 99%
“…Among rare-earth element, many researchers reported that micro-alloying Mg-Zn with yttrium or cerium exhibited a comparable ductility and formability with commercial magnesium alloys. Tables 3 and 4 summarize the mechanical properties of the published alloys in Mg-Zn-Y [154][155][156][157] and Mg-Zn-Ce [48,71,81,85,[156][157][158], respectively. The addition of yttrium to Mg-Zn alloys enhances the formation of magnesium solid solution in ternary systems due to high solid solubility of yttrium in magnesium.…”
Section: Mechanical Properties Of Mg-zn-{ce Y} Alloysmentioning
confidence: 99%
“…Currently, thermodynamic analysis of Mg-Zn-Ce-Zr alloys (Mg-rich angular region) gives information on the formation temperature, transformation reaction equations, and structure of various compounds [12,13]. The addition of Ce improves the yield strength (YS), ultimate tensile strength (UTS), and ductility of the alloy by refining the grains [14], promoting the formation of dynamic recrystallization, forming high density precipitation, and weakening the weave [15]. The mixed addition of Ce and other elements (Y, Ca, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…There have been many reports of high performance Mg-Zn-Ce alloys processed by hot extrusion [13,14] and rolling [15][16][17]. It is found that the Ce/Zn ratio is a crucial factor of mechanical properties of wrought Mg alloy, which have significantly effects on deformation parameters [18], recrystallization behavior [19] and density of precipitates [20]. At present, some high strength Mg-Zn-Ce alloys were developed based on the Mg-(4-7)Zn alloys [13][14][15][16][17]21], however, the detailed microstructure, phase constitution and thermal-stability determined by Ce/Zn ratio were not clarified.…”
Section: Introductionmentioning
confidence: 99%